1970
DOI: 10.33899/edusj.1970.58955
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasites among Patients attending General Central Public Health Laboratory in Erbil City-Iraq during 1998-2004

Abstract: ‫المئوية‬ ‫النسب‬ ‫تعيين‬ ‫و‬ ‫لتقدير‬ ، ‫ة‬ ‫المباشر‬ ‫يقة‬ ‫بالطر‬ ‫الطفيمية‬ ‫اع‬ ‫باألنو‬ ‫لإلصابة‬ . 1380 ‫أصل‬ ‫من‬ ‫از‬ ‫بر‬ ‫عينة‬ 5768 ‫تم‬ ‫نموذج‬ ‫كان‬ ‫فحصها،‬ ‫المعوية‬ ‫بالطفيميات‬ ‫مصابة‬ ‫ت‬ %23.9 . ‫جهة‬ ‫من‬ ‫اإلصابات‬ ‫بين‬ ‫عالية‬ ‫معنوية‬ ‫فروق‬ ‫وجدت‬ ‫لمنتائج،‬ ‫اإلحصائي‬ ‫التحميل‬ ‫خالل‬ ‫من‬ ‫أخرى‬ ‫جهة‬ ‫من‬ ‫المرضى‬ ‫جنس‬ ‫الى‬ ‫نسبة‬ ‫الطفيمية‬ ‫اع‬ ‫األنو‬ ‫يع‬ ‫توز‬ ‫و‬ ‫اسة‬ ‫الدر‬ ‫ات‬ ‫سنو‬ ‫من‬ ‫وكل‬ . ‫كان‬ ‫إصابة‬ ‫نسبة‬ ‫أعمى‬ %42.4 ‫السنة‬ ‫في‬ 1998 ‫أقمها‬ ‫و‬ %5 ‫سنة‬ ‫ف… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For example, in a study that included 500 diarrheal stool samples from infants and children, Entamoeba infections were found in 35% of samples ( Al-Sorchee et al 2013 ). In another study, the infection rate was 51.7%, but this study did not exclude the commensal protozoa Entamoeba coli ( Hamad and Ahmed 2011 ). Unlike the present study, all research that has previously been done in Erbil City was based on samples from symptomatic subjects only, and this may be a reason for the differences in the rate of infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study that included 500 diarrheal stool samples from infants and children, Entamoeba infections were found in 35% of samples ( Al-Sorchee et al 2013 ). In another study, the infection rate was 51.7%, but this study did not exclude the commensal protozoa Entamoeba coli ( Hamad and Ahmed 2011 ). Unlike the present study, all research that has previously been done in Erbil City was based on samples from symptomatic subjects only, and this may be a reason for the differences in the rate of infections.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the PCR technique has never been used for assessing the prevalence rate of E. histolytica in Erbil City. Several studies have reported the infections with E. histolytica in almost all Iraqi cities, but only a few applied molecular methods; most relied on microscopic examination ( Hamad and Ahmed 2011 ; Al-Sorchee et al 2013 ; Saqur et al 2017 ). To date, no research has been conducted on asymptomatic individuals in Iraq, the least-studied group globally.…”
Section: Introductionmentioning
confidence: 99%
“…The two species cannot be separated morphologically. However, they may be identified using a variety of experimental techniques [13,14].…”
Section: Feces Examinationmentioning
confidence: 99%
“…Infections have been documented in several studies. Nearly all Iraqi cities contain E. histolytica, but only a handful have used molecular techniques; the majority rely on microscopic investigation [13]. The least-studied category internationally, asymptomatic people have not yet been the subject of any research in Iraq.…”
Section: Introductionmentioning
confidence: 99%